Myotoxin Inhibitors - Santos-Filho, Norival Alves [UNESP]; Silveira, Lucas Blundi; Boldrini-Franca, Johara; Cruz, L. J.; Luo, S.; Gopalakrishnakone, P. (Springer, 2017)
Myonecrosis is an important medical complication in snake envenoming and, in severe cases, can lead to drastic sequelae, such as inability and permanent tissue loss. Although the traditional serum therapy effectively neutralizes the systemic effects induced by snake venoms, there are some limitations in reversing the local symptoms induced by myotoxins, since they are small- and medium-sized proteins of low immunogenicity. Due to this impairment in current snakebite treatment, there has been an increasing interest in the search for naturally occurring molecules, as well as in the design of synthetic compounds, which are able to inhibit the main pathophysiological effects induced by snake venom PLA(2) and other myotoxins. These inhibitory molecules are mainly obtained from animal blood and plant extracts; however, a diversity of other sources of myotoxin inhibitors has also been described. This chapter aims to provide current information regarding the diversity of natural and synthetic PLA(2) inhibitors described so far. Moreover, a better understanding of the mechanisms of action involved in PLA(2) inhibition may generate perspectives to the use of these molecules leading to the development of novel therapeutic approaches for snakebite management.
Keywords: Myotoxins; Phopholipases A(2); Myotoxin inhibitors